2015
DOI: 10.1371/journal.pone.0118059
|View full text |Cite
|
Sign up to set email alerts
|

Parental Use of Corporal Punishment in Europe: Intersection between Public Health and Policy

Abstract: Studies have linked the use of corporal punishment of children to the development of mental health disorders. Despite the recommendation of international governing bodies for a complete ban of the practice, there is little European data available on the effects of corporal punishment on mental health and the influence of laws banning corporal punishment. Using data from the School Children Mental Health Europe survey, the objective of this cross-sectional study was to examine the prevalence and legal status of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…- the policies banning physical punishment and the parental declaration of spanking their children in case of misbehaviour and to find a negative correlation after controlling for most of the social expected predictors (Durivage 2014) [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…- the policies banning physical punishment and the parental declaration of spanking their children in case of misbehaviour and to find a negative correlation after controlling for most of the social expected predictors (Durivage 2014) [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…As noted earlier, Bussman and colleagues' (2011) cross-sectional comparison of 5,000 parents across five countries - three with bans and two without bans -found that substantially fewer parents reported physically punishing their children in the countries with bans (Austria: 18%; Germany: 17%; Sweden: 4%) than in countries without bans (France: 51%: Spain: 54%). Another cross-sectional study compared parental physical punishment and children's mental health problems by whether the country had (Bulgaria, Germany, Netherlands, Romania) or had not (Lithuania, Turkey) prohibited physical punishment (duRivage et al, 2015). The likelihood of parents reporting frequent physical punishment was 1.7 times higher in countries where it was legal.…”
Section: Legal Prohibition Of Physical Punishmentmentioning
confidence: 99%
“…The likelihood of parents reporting frequent physical punishment was 1.7 times higher in countries where it was legal. Children who were frequently physically punished had higher levels of externalizing and internalizing problems than those who experienced little to no physical punishment (duRivage et al, 2015). …”
Section: Legal Prohibition Of Physical Punishmentmentioning
confidence: 99%
“…In a comparison of six European countries (Bulgaria, Germany, Lithuania, the Netherlands, Romania, and Turkey), parents were 1.7 times more likely to report using corporal punishment in countries in which corporal punishment is legal (duRivage et al, 2015). Zolotor and Puzia (2010) reviewed evidence from the first 24 countries that passed legal bans and concluded that legal bans were associated with decreases in support and use of corporal punishment.…”
Section: Previous Evaluations Of Legal Bansmentioning
confidence: 99%